1954
DOI: 10.1063/1.1740098
|View full text |Cite
|
Sign up to set email alerts
|

The Microwave Spectrum of Vinyl Cyanide

Abstract: The rotational spectrum of the slightly asymmetric top, vinyl cyanide, has been investigated in a microwave spectrograph employing Stark effect modulation and in a direct absorption cell. The rotational constants a=49 076.2 Mc/sec, b=4971.33, and c=4514.05 were computed from the observed frequencies of the J = 2-->3 transitions. From measurements of the Stark effect, the components of the dipole moment were found to be I'a=3.68D, I'b= 1.25, 1'=3.89. Partial resolution of the hyperfine structure of certain line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1961
1961
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These included (HCN) 2 , 41,42 CH 3 CN, 43 CH 3 CCCN, 44,45 HC 3 N, [46][47][48] HC 5 N, 49 HC 7 N, 50 HC 9 N, 51 ICN, 52 ICCCN, 53 CH 2 (CN) 2 , 54,55 cyanoallene, 56,57 and vinyl cyanide (CH 2 = =CHCN). 58,59 There was evidence of (H 2 O) 2 , which is presumed to be a result of the contamination of the gas lines behind the valve by small amounts of H 2 O impurity. 60 Figure 3 shows the spectra recorded in both regions after removal of peaks corresponding to the fragments listed above.…”
Section: A Qualitative Observationsmentioning
confidence: 99%
“…These included (HCN) 2 , 41,42 CH 3 CN, 43 CH 3 CCCN, 44,45 HC 3 N, [46][47][48] HC 5 N, 49 HC 7 N, 50 HC 9 N, 51 ICN, 52 ICCCN, 53 CH 2 (CN) 2 , 54,55 cyanoallene, 56,57 and vinyl cyanide (CH 2 = =CHCN). 58,59 There was evidence of (H 2 O) 2 , which is presumed to be a result of the contamination of the gas lines behind the valve by small amounts of H 2 O impurity. 60 Figure 3 shows the spectra recorded in both regions after removal of peaks corresponding to the fragments listed above.…”
Section: A Qualitative Observationsmentioning
confidence: 99%
“…Acrylonitrile is a molecule with a strong rotational spectrum, which has been the subject of many, successively more refined studies [1][2][3][4][5][6][7][8][9][10][11][12]. Much of that work has been stimulated by the astrophysical relevance of acrylonitrile, and it has been demonstrated that transitions in interstellar 13 C isotopic acrylonitrile can also be detected [10].…”
Section: Introductionmentioning
confidence: 97%
“…Acrylonitrile (vinyl cyanide, H 2 C@CHCN) is a relatively rigid planar molecule, and its laboratory rotational spectrum has already been studied on numerous occasions [1][2][3][4][5][6][7][8][9][10]. Acrylonitrile is also an established astrophysical species (see Ref.…”
Section: Introductionmentioning
confidence: 99%